2013
DOI: 10.1088/0004-637x/769/1/79
|View full text |Cite
|
Sign up to set email alerts
|

GALAXY CLUSTERS AROUND RADIO-LOUD ACTIVE GALACTIC NUCLEI AT 1.3 <z< 3.2 AS SEEN BYSPITZER

Abstract: We report the first results from the Clusters Around Radio-Loud AGN (CARLA) program, a Cycle 7 and 8 Spitzer Space Telescope snapshot program to investigate the environments of a large sample of obscured and unobscured luminous radio-loud AGN at 1.2 < z < 3.2. These data, obtained for 387 fields, reach 3.6 and 4.5 µm depths of [3.6] AB = 22.6 and [4.5] AB = 22.9 at the 95% completeness level, which is two to three times fainter than L * in this redshift range. By using the color cut [3.6]-[4.5] > −0.1 (AB), wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
341
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(360 citation statements)
references
References 73 publications
18
341
0
1
Order By: Relevance
“…Current literature will often forego the first requirement, particularly for distant clusters, due to the challenges of acquiring such data-and this is particularly problematic for our RLAGN targets due to Inverse Compton scattering of the cosmic microwave background by the hot plasma associated with AGN radio lobes into the X-ray regime. Nonetheless, we show that some CARLA systems have clear overdensities of passive galaxy candidates (see also Cooke et al 2015;Cooke et al 2016, in preparation), and Wylezalek et al (2013) show that the CARLA cluster member candidates are, on average, centrally concentrated around the target RLAGN.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Current literature will often forego the first requirement, particularly for distant clusters, due to the challenges of acquiring such data-and this is particularly problematic for our RLAGN targets due to Inverse Compton scattering of the cosmic microwave background by the hot plasma associated with AGN radio lobes into the X-ray regime. Nonetheless, we show that some CARLA systems have clear overdensities of passive galaxy candidates (see also Cooke et al 2015;Cooke et al 2016, in preparation), and Wylezalek et al (2013) show that the CARLA cluster member candidates are, on average, centrally concentrated around the target RLAGN.…”
Section: Introductionsupporting
confidence: 66%
“…In particular, as discussed in Section 1, other hallmarks of a bona fide cluster include a significant population of evolved massive galaxies and a centrally concentrated distribution of galaxies. We show in Section 5.2.1 that CARLA J2039−2514 contains an overdensity of (spectroscopically unconfirmed) red galaxies with properties consistent with being passive galaxies at the redshift of the structure, and prior work by our team has demonstrated that the color-selected (i.e., red) candidate cluster members are centrally concentrated around the target RLAGN (Wylezalek et al 2013). The overdensities reach s 9.0 and s 7.8 above the field value for the fields around MRC 2036−254 and B30756+406, respectively.…”
Section: Cluster Membershipmentioning
confidence: 68%
See 1 more Smart Citation
“…Additionally, their radio-loud sample shows a larger clustering amplitude than their radio-quiet sources. Previous observations at low and intermediate redshift of the environments of radio galaxies and radio-loud AGNs suggest that these reside in denser regions compared with control fields (e.g., Miley et al 2006;Wylezalek et al 2013). At z 1.5, Mpc-sized dense regions have not yet virialized within a single cluster-sized DMH and are consider to be the progenitors of present day galaxy clusters (Kurk et al 2004;Miley & De Breuck 2008).…”
Section: Introductionmentioning
confidence: 93%
“…A large number of imaging and spectroscopic studies have demonstrated conclusively that many massive radio galaxies at z ≥ 2 are surrounded by galaxy overdensities at the same redshift, as well as significant reservoirs of molecular, atomic, and ionized gas, including diffuse intra-halo gas (Le Fèvre et al 1996;Venemans et al 2007;Hayashi et al 2012;Galametz et al 2012;van Ojik et al 1997;Villar-Martín et al 2003;De Breuck et al 2003;Nesvadba et al 2009;Wylezalek et al 2013;Collet et al 2015). With the small field of view of only 8 × 8 , SINFONI can only constrain the very nearby environment of HzRGs out to a few tens of kpc (8 correspond to 64 kpc at z ∼ 2); however, this small-scale environment is particularly interesting, e.g., to study how accretion and merging may affect the evolutionary state of the radio galaxy.…”
Section: Additional Line Emitters and Dynamical Mass Estimates Of Ourmentioning
confidence: 99%